Implementation of the Poetry Method in Assessment the Tahfidz Al-Qur'an Learning in Indonesia - Muhammad Ripin Ikhwandi; Kusaeri Kusaeri; M. Baihaqi; Nur Millah Muthohharoh; Bassam Abul A'la (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
The purpose of this study was to analyze the implementation of the assessment of Al-Qur'an learning by using the poetry method. The approach used in this research is a qualitative approach using the descriptive-analytical method. The results of this study reveal that the assessments used in tahfidz Qur’an learning with the poetry method are the mid-semester assessment (PTS) and the end-semester assessment (PAS). The form of assessment used is an oral test in the form of a sima’ reading test, verse-connecting test, and a comprehensive test. This assessment is carried out 4 times a year. Students are declared passed when they get a minimum score of B with a minimum score of 81 and vice versa are declared to repeat when they get a C score with a score of 70. This assessment is not only on memorizing the Qur'an but memorizing poems is also assessed by the examiner. The findings in this study indicate that students have quite good abilities when tested using the sima' reading test. Students are lower in their abilities if they are tested by verse-connecting questions. Then students have a very low ability if tested using a comprehensive test.